Surveillance of pathogenic Leptospira among rodents and small mammals in enzootic areas of plague in Pasuruan Indonesia - Febriani, Siti Amanah; Dhanti, Kurnia Ritma; Kurniawan, Kurniawan; Ristiyanto, Ristiyanto; Junaedi, Arief; Sukowati, Caecilia Hapsari Ceriapuri; Handayani, Farida Dwi (Faculty of Medicine, Universitas Islam Sultan Agung (UNISSULA), Indonesia, 2024)
Leptospirosis is a globally significant yet often overlooked zoonotic infection. Several regions in Indonesia are endemic for leptospirosis, including East Java. Pasuruan a region located in the East Java province of Indonesia, has been recognized as an enzootic area of plague infection. However, the presence of other rodent-borne diseases has not been reported. This study aims to detect the presence of pathogenic Leptospira in rats and small mammals in the enzootic plague area of Pasuruan in Indonesia. This study belongs to the type of observational analytic research with a cross-sectional study design. Simple random sampling was conducted to trap a total of 119 forms 107 rats and 12 small mammal kidneys were analyzed molecularly (PCR) to detect Leptospira bacteria with the LipL32 gene as the target. The study revealed that 7.6% (9/119) of rats in the enzootic areas of plague (Sedaeng, Tosari, Surorowo, Petren, Pakis Bincil, Kutukan) were found to carry Leptospira DNA, indicating a significant difference between infection rates per region (p < 0.0001). Rattus tanezumi was identified as the Leptospirosis reservoir in settlements habitats with a percentage of 13.2%, Rattus tiomanicus was detected at 28.6% in forest habitats, and Rattus exulans was found at 4.4% in both habitats. The findings in our study, it is crucial for the community to increase awareness of the spread of rodent-borne diseases, including Leptospirosis.